Elevated Serum Ceruloplasmin Levels Are Associated with Higher Impulsivity in People with Parkinson’s Disease - Megan C. Bakeberg; Maddeson Riley; Michelle Byrnes; Alexa Jefferson; Souyma Ghosh; Malcom K. Horne; Sarah McGregor; Rick Stell; Sue Walters; Tess Evans; Katherine Roberts; Frank L. Mastaglia; et al. (Parkinson's Disease)
Background. Heightened impulsivity has been reported in a subset of people with Parkinson’s disease (PwP) and is considered a risk factor for the development of impulse control disorders (ICDs). However, at present, there are no recognised biochemical markers of heightened impulsivity. Objectives. To determine if ceruloplasmin, a serum marker involved in the regulation of iron and copper homeostasis, is associated with trait impulsivity in PwP. Methods. The study measured serum ceruloplasmin and impulsivity using the Barratt Impulsiveness Scale (BIS-11) in an Australian cohort of 214 PwP. Multivariate general linear models (GLMs) were used to identify whether higher serum ceruloplasmin levels (>75th percentile) were significantly predictive of BIS-11 scores. Results. Serum ceruloplasmin was higher in females with PD (p<0.001) and associated with MDS-UPDRS III, Hoehn and Yahr, and ACE-R scores (p<0.05). When correcting for covariates, higher serum ceruloplasmin concentrations were associated with the 2nd order nonplanning impulsivity and with the 1st order self-control and cognitive complexity impulsivity domains. Conclusions. Higher serum ceruloplasmin levels are independently associated with heightened nonplanning impulsivity in PwP. Thus, serum ceruloplasmin levels may have clinical utility as a marker for heightened impulsivity in PD.